Features of Metaphors in Shaukat Rahman’s Poetry - Z. Sh. Ashurova (Research Parks Publishing LLC, 2023)
The article reflects on metaphor, and notes that the study of metaphor has been analyzed, in particular, by representatives of such sciences as rhetoric, psychology, philosophy, stylistics, literary criticism, translation studies and even cybernetics.